Performance of Finnish Hedge Funds, evidence from the financial crisis and post-crisis period - Konkarikoski, Oskari (My University, 2018)
Hedge funds are alternative investment vehicles which aim at absolute returns in every market situation and impose active trading strategies. Hedge funds are less regulated than traditional mutual funds and therefore they have no restrictions in usage of derivatives, short selling and leverage. The purpose of this study is to evaluate the performance of Finnish hedge funds during the most severe part of the financial crisis, August 2007 – March 2009, and during the long bullish post-crisis period, April 2009 – July 2017. The data of this study consists of monthly returns of totally 37 Finnish hedge funds. The performance is measured with raw returns and risk-adjusted returns and they are also compared to different benchmark indices. Also the exposure of Finnish hedge funds to market movements is evaluated with regression analysis. Additionally, the impact of different characteristics of Finnish hedge funds to their risk-adjusted performance is measured with regression analysis. The empirical results in this study show that Finnish hedge funds could not achieve absolute returns during the financial crisis but they outperformed OMX Helsinki index and the global Barclay Hedge Fund Index in terms of raw returns and risk-adjusted returns. During the bull period, Finnish hedge funds performed poorly on average, having worse raw returns and risk-adjusted returns than OMX Helsinki index and Barclay Hedge Fund Index. Risk exposure of Finnish hedge funds to market movements were low during both crisis and bull periods. According to regression analysis in this study, age of a Finnish hedge fund seems to have a positive impact to risk-adjusted performance while high management fees have a negative impact to risk-adjusted returns during the bull period. The findings of this study indicate that Finnish hedge funds have lower standard deviations than market index but most of the funds face also significantly lower returns. Therefore, Finnish hedge funds are less risky investment vehicles and may offer alternative choice for investors who look for less risky asset class than stocks. Finnish hedge funds may also offer diversification benefits, due to their low exposure to market indices.
Keywords: Hedge funds; performance; risk-adjusted return; risk exposure; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|